A liquid chromatography–tandem mass spectrometry method for the determination of cocaine and metabolites in blood and in dried blood spots collected from postmortem samples and evaluation of the stability over a 3‐month period. Issue 9 (25th May 2018) - Moretti, Matteo; Visonà, Silvia Damiana; Freni, Francesca; Tomaciello, Ilaria; Vignali, Claudia; Groppi, Angelo; Tajana, Luca; Osculati, Antonio Marco Maria; Morini, Luca
Abstract: The aims of this study were (1) to identify and quantify cocaine (COC), benzoylecgonine (BE), ecgonine methyl ester (EME), and cocaethylene (CE) in DBS; (2) to compare dried blood spots (DBSs) analytical results with the routine blood analyses; (3) to monitor analytes stability on DBS within a 3‐month period. Eighty‐five μL of blood from postmortem cases were put on a card for DBS analysis and kept in the dark, at room temperature. Samples were extracted through solid‐phase extraction (SPE) cartridges and injected in the liquid chromatography–tandem mass spectrometry (LC–MS/MS) system. The analytical procedure is simple, sensitive, and specific. Limits of detection (LODs) and quantification (LOQs) were calculated at 1.0 and 5.0 ng/mL(g) for COC and CE, and at 0.5 and 2 ng/mL for EME and BE, respectively. Validation parameters fulfilled all the acceptance criteria. Fifty‐five postmortem cases were evaluated. Eighteen cases were positive for COC (44–2456 ng/mL) and BE (228–4700 ng/mL), 12 for EME (92–1500 ng/mL), and 11 cases for CE (11–273 ng/mL). Stability was evaluated on 8 cases collected in the period January 2017–January 2018. For each case, 5 DBSs were collected at T0. Four DBSs were analyzed within the 4 following weeks and 1 sample was analyzed after 3 months. The concentrations on DBSs, stored at room temperature, always matched the ones obtained on blood samples kept at −20°C (<20% variation, both at T0 and after 3 months). BE and COC concentrations remained stable after a 3‐month storage, EME concentrations slightly increased after 3 weeks in the 2 analyzed samples, while CE provided a less homogeneous stability depending on the sample. Abstract : We successfully developed and validated an LC–MS/MS method for the identification and quantification of cocaine and metabolites in whole blood and DBS. The results provided a good qualitative and quantitative correlation between DBS and blood.